Feeless Micropayments as Drivers for New Business Models: Two Exemplary Application Cases - Klein, Marvin; Stummer, Christian (Frontiers in Blockchain, 2021)
Upcoming cryptocurrency approaches claim to enable feeless micropayments. Assuming that this promise will be kept, this is likely to give rise to new business models that entail transactions worth fractions of a cent. In this mini review, we describe two exemplary application cases and outline the associated research activities for each. The first case considers subscription models in consumer markets for which feeless micropayments might be used to expand and, thus, enrich the range of plans by offering shorter subscription times. The second case is concerned with prosumers who might be willing to sell self-generated data (e.g., data generated through their smart meters).